Luminous measurement of LED lights in cost effective way - Halim, Abdul; Billah, Abdul Shakib; Jahan, Ishrat (BRAC University, 2014)
This thesis report is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Electrical and Electronic Engineering, 2014.